Mandibular osteonecrosis and the use of bisphosphonate in an oncologic patient: case report (Research, Society and Development, 2022)
Clinical case report of a patient who remains under medical oncology care due to bilateral malignant neoplasm of the breast with bilateral bone and lung metastasis, who developed difficult-to-manage mandibular osteonecrosis related to prosthetic oral trauma and the use of injectable bisphosphonates. This study was carried out in the dentistry service of the Oncology Center of the Oswaldo Cruz University Hospital of the University of Pernambuco. It was possible to take care of, favor and monitor the self-resolving of mandibular bone necrosis for two years, providing oral comfort and the absence of infection, without interruption of hormonal antineoplastic treatment; regardless of the initially proposed peripheral osteotomy procedure to be performed under general anesthesia, it was refused by the patient and family. The autonomy of the patient was respected, and thus, the Standard Operating Protocol for Oral Care (POP-Oral), by Vidal, 2012, associated with antibiotic and analgesic therapy, for three months, and then remained only with POP-Oral and biweekly applications 0.2% chlorhexidine gel until spontaneous expulsion of necrotic bone and excellent healing occurred. Currently, the patient remains under follow-up, remaining without symptoms or any other oral alteration. It is concluded that the treatment of osteonecrosis of the jaws is of great complexity, and there is still no specific treatment, but it is possible to contain, avoid infections and stabilize the evolution of bone lesions, with individualized care, a multidisciplinary team and the exercise of bioethics, in medical-dental practice, as can be seen in this report.